Test of the Different Proportions of Moringa oléifera fluor on the Growth of COBB500 Chicks in Vivo in Kinshasa (DR Congo) Bay - Munganga Kabate Serge; Kalala Gaëtan; Ebwa Joël; Chady Lusia Indila (Britain International for Academic Research (BIAR) Publisher, 2023)
In Kinshasa, to understand the influence of different proportions of Moringa incorporated into the feeding of chicks, a study was carried out on the COBB 500 chicks. 40 chicks with an average weight of 41 ± 4.71 g for the control and 42 ± 4.06 for the test batch were tested in an experimental system duplicated with foods containing 25% crude protein where diets were supplemented with 5%, 10%, and 15% of the Moringa flour for 21 days. After analysis of the results, we noted the following: It was found that the chicks triplet weight during the experiment in the following order: 152 ± 55.96 g for R1, 181 ± 57, 48 g for R2, 185 ± 46.36 g for R3 and 157.5 ± 27.88 g for feed R0. A non-significant difference (>0.05) was found in the STUDENT t-test, between the body weight gain of chicks fed R0 diet and those fed R1, R2, and R3. SGR (specific growth rate) was significantly correlated with the R3 regimen. Weekly consumption was not constant, and with significant increase during the experimental period. The results of mortality rates obtained during this experiment did not seem to be directly linked to the different regimes but rather to diseases, poor zootechnical construction conditions, and untimely shutdown of electricity in livestock premises. Regarding food Conversion Efficiency (ACE), it is found that diets containing 15% of Moringa show better feed conversion efficiency, with 0% diets showing a decrease in diet as the proportion in Moringa decreases. As regards the quantity of the food consumed, it should be noted that R1 was the most consumed during the experiment.